2021
DOI: 10.1029/2020ja028569
|View full text |Cite
|
Sign up to set email alerts
|

Electrodynamical Coupling of the Geospace System During Solar Flares

Abstract: Reduced daytime upward E×B drifts and weakened fountain effects in equatorial ionosphere have been frequently observed during the initial stage of solar flares. The cause of this phenomenon, however, remains unresolved. The latest state‐of‐art whole geospace model provides an unprecedented opportunity to explore the origin of this response. We show that both prompt penetration electric fields (PPEFs) and internal changes in the wind dynamo process are responsible for the reduced upward ion drifts. Solar‐flare‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…In order to maintain global current continuity, the low-latitude zonal electric field must weaken during flares. The weakened eastward electric field causes weakened ionospheric vertical drift and weakened fountain effect during flares, as observed (Liu et al, 2020). The weakened ionospheric vertical drift changes the vertical distribution of plasma density, thus changing the radio signal reflection height.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In order to maintain global current continuity, the low-latitude zonal electric field must weaken during flares. The weakened eastward electric field causes weakened ionospheric vertical drift and weakened fountain effect during flares, as observed (Liu et al, 2020). The weakened ionospheric vertical drift changes the vertical distribution of plasma density, thus changing the radio signal reflection height.…”
Section: Discussionmentioning
confidence: 60%
“…Liu et al. (2020) examined mechanisms of weakened upward ion drift during the initial phase following an X‐class solar flare. They found that sudden enhancements in electron density following solar flares increase both Hall and Pedersen conductivities.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 7 shows that the flare‐induced reduction of daytime zonal electric fields was caused predominantly by conductivity changes. Several studies (Liu, Qian, et al., 2021; Xiong et al., 2014; Zhang et al., 2017, 2019) suggested that this reduction at the dip equator might be associated with an increased normalΣH/normalΣP that caused an increase in the Cowling conductance. The flare enhanced the equatorial Cowling conductance, which was relatively greater than the increase of global dynamo source currents that is suggested to scale with the Pedersen conductance increase.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 10, the comparison of the equatorial zonal electric fields from Run 4 to Run 2 (Run 2–Run 4) show the impacts of the flare‐increased normalΣP and normalΣH. Since the conductivity responses decrease with altitudes and the peak height of the Hall conductivity is lower than that of the Pedersen conductivity, normalΣH/normalΣP is enhanced by solar flares and further induces the electrodynamic variations (Liu, Qian, et al., 2021; Xiong et al., 2014). However, the effects of the normalΣH/normalΣP enhancement by the flares are much smaller than the influences of the bold-italicUnormalΣ changes caused by the flares (Figure 10), this is different from the previous explanation that the enhancement of equatorial Cowling conductivity, normalΣP(1+ΣH2/ΣP2), is the major factor that causes the daytime electric field reduction (Liu, Qian, et al., 2021; Xiong et al., 2014; Zhang et al., 2017, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation